Hold your fingers: the communication ethics on whatsapp based on the Hadith - Uswatun Hasanah; Busro Busro (Penerbit Universiti Kebangsaan Malaysia, 2023)
In recent years, the widespread dissemination of false information on social media, especially WhatsApp, has become a major concern. This calls for a comprehensive analysis, emphasizing the Hadith perspective, in the context of Covid-19 misinformation in Indonesia. This article qualitatively analyses the spread of false information through WhatsApp, from the Hadith perspective. This study collected and analyzed WhatsApp messages circulating in Indonesia from 2020 to 29 May 2022, using the Turnbackhoax website to identify false information related to COVID-19. There were 217 messages classified into various categories, such as understanding COVID-19, symptoms, government policies, services, spread, treatment, positive patient data, task force, deaths, economic, social, and religious impacts, vaccines, and masks. The findings show that WhatsApp is a social media platform that is widely used to spread false information. The findings were then analyzed using Hadith, which revealed WhatsApp communication ethics such as silence is better than communicating false information, selectively sharing information, and conducting investigations. This research is expected to contribute to understanding the method in clear standardization, namely the Hadith of the Prophet. Anyone can use this method to prevent the spread of false information through various mass communication media, not only WhatsApp.